Biosynthesis of core–shell α-Fe2O3@Au nanotruffles and their biomedical applications - Alijani, Hajar Q.; Fathi, Amirhossein; Amin, Hawraz Ibrahim M.; Lima Nobre, Marcos Augusto [UNESP]; Akbarizadeh, Majid Reza; Khatami, Mehrdad; Jalil, Abduladheem Turki; Naderifar, Mahin; Dehkordi, Farhad Safarpoor; Shafiee, Ali (Springer Nature, 2022)
Core/shell Fe@Au nanostructures with their unique physicochemical properties have been widely studied in a wide variety of biomedical programs, such as imaging, biosensing, hyperthermia, drug delivery, and tissue engineering. Core/shell hematite (α-Fe2O3)@Au nanotruffles were synthesized using Rosmarinus officinalis leaf extract as natural reducing agent. First, hematite (α-Fe2O3) nanoparticles were fabricated using phenolic compounds in rosemary extract. Then, the Au nanoparticles were coated on the α-Fe2O3 core nanoparticles without utilizing any intermediate material. The physicochemical properties of the Fe2O3@Au nanotruffles were evaluated by XRD, FTIR, FESEM-EDAX, HR-TEM, and XPS. Due to the specific morphology of Fe2O3@Au nanotruffles, the Au shell thickness varied from 2.3 to 9 nm in different regions. The toxicity of the core/shell α-Fe2O3@Au nanotruffles with different concentrations was evaluated on human glioblastoma U87 cancer and PC12 pheochromocytoma cells based on MTT assay. The results established that these nanotruffles had the high toxicity effect on glioblastoma cells at a concentration of 500 μg/mL. Additionally, their antibacterial was evaluated on Escherichia coli and Streptococcus mutans by using the dilution method. Graphical Abstract: [Figure not available: see fulltext.].
Keywords: Bimetallic; Cell line; Core–shell, α-Fe2O3@Au nanotruffles; Nanoparticles, Nanostructure, Synthesis; Toxicity, cancer therapy